2020
DOI: 10.1111/ipd.12611
|View full text |Cite
|
Sign up to set email alerts
|

Hall technique crowns and children's masseter muscle activity: A surface electromyography pilot study

Abstract: Background Hall technique crowns (HTCs) alter the occlusion temporarily, potentially affecting jaw muscles, particularly the masseter – the primary jaw‐closing muscle. Aim To assess masseter muscle activity (MMA) in children treated with a unilateral HTC. Design In 12 children treated with a single HTC, bilateral MMA was recorded with surface electromyography (sEMG) for ten cycles of Rest Position (RP) and Maximum Voluntary Clenching (MVC) over 20 seconds immediately pre‐HTC cementation (Pbase), immediately po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“… 34–36 Other reported problems in pilot studies related to the Hall technique include TMJ symptoms, reduction in masseter muscle activity, and extrusion of newly erupted permanent molars. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“… 34–36 Other reported problems in pilot studies related to the Hall technique include TMJ symptoms, reduction in masseter muscle activity, and extrusion of newly erupted permanent molars. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…One concern over the use of the HT is that the raised occlusion resulting from no occlusal reduction would lead to changes in muscle activity, temporomandibular joint dysfunction and masticatory difficulties post‐treatment. To address these concerns, bilateral masseter muscle activity on clenching measured with surface electromyography and bite force in children who had PMCs placed with the HT was evaluated 29,30 . There was increased muscle activity 29 and reduced bite force 30 immediately post‐treatment, but both measures returned to baseline levels by 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pilot study investigated the effect of the Hall technique crown application on the masseter muscle activity. The study concluded that Hall technique crowns might affect masseter muscle activity in children immediately post-treatment, but the activity returned to and later exceeded baseline levels at 2-6 weeks, respectively, while the rest masseter muscle activity remained unchanged (Abu Serdaneh et al 2020). In addition, the HT was found to be more cost-effective than the conventional surgical method of treatment.…”
Section: The Hall Techniquementioning
confidence: 94%